The importance of folic acid for the health of the human body - Karolina Jolanta Banyś; Monika Wioletta Knopczyk; Barbara Bobrowska-Korczak (Farmacja Polska, 2020)
A well-balanced diet is undoubtedly a key factor to maintain your body's normal state of health. A deficiency or excess of any nutrient can cause negative effects on human health. Folic acid is one of the elements of the diet, which is often supplied in insufficient quantities. This vitamin and its derivatives participate in the metabolism of amino acids and nucleic acids. Therefore, it is necessary for the proper functioning of the body's cells and for maintaining homeostasis, especially of the nervous, circulatory and cardiovascular systems. The biological activity of folic acid and its derivatives essentially affects the metabolism of important amino acids, such as methionine, homocysteine, serine, glycine, pyrimidine and purine synthesis and DNA methylation. The synthetic form of folic acid (most oxidized), which can be found in fortified foods, dietary supplements or pharmaceuticals, does not show biological activity. It is transformed in a series of reactions with the participation of many enzymes to form folates, which differ in the number of glutamic acid residues and the degree of oxidation. The actively biological form is reduced folate (L-5-MTHF), which is transported together with the blood to cells where it undergoes biological processes important for our health. The MTHFR gene, coding for the enzyme protein of the same name - methylene tetrahydrofolate reductase, is located on chromosome 1 at the 1p36.3 locus. This protein is responsible for the catalysis of the enzymatic reaction, which is the reduction of 5,10-methylenetetrahydrofolate to L-5-methyltetrahydrofolate, i.e. the active form of folate. This form is necessary in the process of homocysteine degradation, in the aftermath remethylation to methionine. This protein is responsible for the catalysis of the enzymatic reaction, which is the reduction of 5,10-methylenetetrahydrofolate to L-5-methyltetrahydrofolate, i.e. the active form of folate. This form is necessary in the process of homocysteine degradation, in the aftermath remethylation to methionine. However, according to available literature, mutation of the MTHFR 677C> T gene occurs in even 53% of the population. Among carriers of the TT genotype, it can cause about 70% reduction of MTHFR reductase activity. It is especially dangerous for people who do not provide adequate amounts of folic acid along with their diet and for those who need a high amount of this vitamin, e.g. due to taking medications that reduce its absorption, i.e. metformin or oral contraceptives. Many people metabolize folic acid on insufficient levels. For medical reasons, not the mutation itself is a problem, but too low the folate levels. In recent years, there is more and more discussion about the active form of folic acid and the possibility of effective supplementation with metapholine, which is a combination of calcium with L-5-MTHFR. It is a natural and reduced form of folate, which hydrolized and then transforms into L-5-MTHFR. Metapholine, in comparison to folic acid, is not reduced to be incorporated into metabolic processes in the cell, which is catalyzed by DHFR and MTHFR enzymes. In addition, the absorption of the active form of folic acid is faster because some metabolic pathways are missed. This is particularly important for people who have a MTHFR gene mutation homozygous with 665C> T and / or 1298A> C polymorphism and a mutation of the DHFR gene with 458A> T polymorphism. Numerous clinical studies have confirmed the efficacy and safety of the active form of folic acid. In a study by Houghton et al., which was conducted among pregnant Canadian women, L-5-MTHFR was shown to be at least as effective in lowering homocysteine levels as folic acid supplementation. In addition, the active form of folic acid was more effective at storing folate in erythrocytes. In a study conducted by Lamers et al. on 135 women after a period of 24 weeks, L-5MTHR was shown to be a suitable alternative in reducing plasma homocysteine levels compared to folic acid and placebo. In addition, Bentley et al. analyzed the results of 112 pregnant women from the USA. Patients were assigned to two groups in which each took vitamin B12. In addition, in one of them women supplemented with L-5-MTHFR, and in the other - folic acid. The results showed that patients who supplemented the active form of folic acid not only had higher hemoglobin levels, but also less often had anemia. When analyzing clinical trials of patients with the MTHFR mutation, the same trend was observed. Metafoline increased plasma folate levels and decreased homocysteine levels. In one study on German women, there was a decrease in homocysteine levels and an increase in folate levels in both plasma and red blood cells in patients who supplemented the active form of folic acid. In another study involving Swiss patients with the current 677CC MTHFR or 677TT MTHFR mutation, it was demonstrated that using L-5-MTHFR significantly reduces homocysteine levels compared to folic acid. It is also worth mentioning that Prinz-Langenhol et al. in a study on women with the 677CC and 677TT mutations proved that the active form of folic acid has a better effect on increasing folate levels than folate. It is also worth mentioning that folic acid at high doses can mask ailments or even diseases caused by vitamin B12 deficiency. In addition, folic acid administered at high doses in patients with the MTHFR mutation is not reduced to an oxidized, inactive form and is not properly transported to plasma. Non-metabolised folic acid can be dangerous to the human body and contribute to the development of cancer. Supplementation, in particular the active form of folic acid, should be considered by patients who are carriers of the MTHFR or DHFR mutation. In addition, the use of stimulants such as alcohol or nicotine also negatively affects the absorption of this vitamin. Taking some medications weakens the absorption of folic acid - these include folic acid antagonists, anti-tuberculosis drugs, hormonal oral contraceptives, nonsteroidal anti-inflammatory drugs or metformin widely used. Folic acid is necessary for the proper functioning of the human body and its deficiency may induce various disease processes in the body, which include: the formation of neural tube defects, disorders in the nervous system, megaloblastic anemia, a negative effect on the functioning of the cardiovascular system and the development of atherosclerosis and cancer. More and more people have anemia, including megaloblastic anemia, which is characterized by abnormal nucleic acid synthesis. The consequence of too low folate levels is impaired red blood cell production, an increase in their volume, and premature death. Extremely dangerous is megaloblastic anemia, the so-called malignant anemia in pregnant women, as it can lead to serious complications such as hemorrhage, infection, and even intrauterine fetal death. A significant influence of folic acid on the functioning of the nervous system has been proven in many clinical studies. This vitamin is involved in the formation of important neurotransmitters such as: adrenaline, dopamine and noradrenaline, therefore its deficiency may lead to the development of neuropsychiatric disorders (dementia, epilepsy, depression and psychosis). These disorders are often caused by high levels of homocysteine, which is not properly metabolized to methionine due to folate deficiency. An excess of homocysteine, as a consequence, leads to atherosclerosis in the cerebral arteries and, as a result of insufficient blood supply, transient ischaemic attack occur, which can contribute to the development of dementia or Alzheimer's disease. Nutritional observations indicate that eating fresh vegetables rich in folic acid protects against the formation of some cancers, e.g. large intestine, breast, ovary, uterus, lungs, pancreas. Deficiency of folic acid promotes the activation of protooncogenes to oncogenes, which in consequence results in a decrease in the stability of cellular DNA. A study carried out by Giovannicci et al. showed that excessive alcohol consumption and folic acid deficiency associated with it increased the risk of developing colorectal cancer by almost four times. However, what cannot be overlooked, the results of clinical trials show us that very high doses and folic acid accumulation favor the development of some cancers. It is thought that excess of folic acid may lead to hypermethylation of DNA and, consequently, to inactivation of the suppressor genes responsible for controlling cell division. Women in the pre-contraceptive period, during pregnancy and breastfeeding are included in the group of people with a special need for folic acid, in whom deficiency can cause many negative effects. The presence of folic acid is necessary in the process of cell formation and growth in the developing fetus, especially when the neural tube is forming. Moreover adequate folic acid concentration decreases risk of fetal heart and urinary tract defects, and also reduces the occurrence of thrombosis and miscarriage in pregnant women. Steeweg-de Graaff J. et al. conducted evaluation of emotional and behavioral development at the age of 3 depending on the concentration of folates and homocysteine in the mother's blood plasma at an early stage of the pregnancy. It was noted that with insufficient folate supply, associated with a lack of or its late supplementation increases the risk of emotional problems in children. In addition, defects of the nervous system may occur as a result of dysfunction of folate metabolism. In its transformation pathway MTHFR reductase takes a particular role. Its reduced activity contributes to the impairment of folic acid metabolism, and the MTHFR gene - type 677CC is considered a risk factor for the development of neural tube defects. Randomized study compared pharmacokinetic parameters of [6S]-5-MTHF and folic acid in healthy women of childbearing age with different MTHFR genotypes (677TT n = 6, 677CC n = 8). Higher peak folate concentrations in plasma with [6S]-5-MTHF supplementation was found, in comparison with folic acid and not depending in the MTHFR genotype, as well as a shorter time needed to reach maximum concentration. In a different randomized, double-blind trial significantly higher folate levels in red blood cells were obtained in women receiving [6S]-5-MTHF. Studies confirm the hypothesis that nutritional deficiencies are of great importance in terms of fetal development. The results testify the need of folic acid supplementation, in which it is worth to consider the use of biologically active form, 12 weeks before planned pregnancy. In the second and third trimesters, the supplementation of folic acid is an important element in prevention of anemia caused by vitamin B12 and folic acid deficiency, i.e. megaloblastic anemia. Moreover, it was found that folic acid at a daily dose of 400 - 800 μg reduce the risk of fetal neural tube defects. In its guidelines, Polish Society of Gynecologists and Obstetricians (PTGiP) recommends supplementation of 400 μg / day of folic acid in women in low risk group in the pre-contraceptive period, pregnancy and during breastfeeding and supplementation of 800 μg/ day of folic acid in women in intermediate risk group and also high risk group in II and III trimester and during breastfeeding. It is worth emphasising that in most recent guidelines, PTGiP pays attention to the problem of folic acid metabolism and emphasizes the appropriateness of supplementation with its active form, especially at high doses. In folic acid metabolism, MTHFR catalyzes the synthesis to the active form of folate (L-5-MTHFR). It is necessary in the process of homocysteine degradation following remethylation to methionine. Unfortunately, as a result of inappropriate methylation, e.g. as a result of active form of folic acid deficiency, the concentration of homocysteine in the blood serum increases, which is responsible for various pathogenic processes in the body. Insufficient supply and improper metabolism of folic acid, as well as vitamins B6, B12 deficiency may be factors favorable for development of atherosclerosis and other diseases related to the cardiovascular system (e.g. heart attack, stroke, coronary artery disease). Excessively high concentration of homocysteine in the blood plasma, caused by disorders of its metabolic pathway in the body, is one of the reasons for the formation of atherosclerotic changes in blood vessels. Excess of homocysteine, with a simultaneous deficiency of folate and vitamin B12, damages the endothelium of blood vessels and increases oxidation processes, which are associated with the development of inflammation, oxidation of LDL cholesterol and change in the structure of the walls of blood vessels. In addition, the risk of developing peripheral thrombosis and hypertension increases. In the meta-analysis of Linda L. et al. it was found that high concentration of homocysteine is an independent factor of developing coronary heart disease. In the majority of studies, the risk of this disease is increased by 20% to 50% with every increase of concentration of homocysteine by 5 μmol /L in the blood of the examined persons. To ensure proper functioning of blood vessels and to reduce the risk of cardiovascular disease, one needs to provide adequate concentration of homocysteine in the body. Folates and their adequate supply with diet or supplementation play a key role in this process. Looking at the numerous clinical studies, available literature and the function of folic acid, it can be stated that it is an essential compound with multidirectional biological action, which is involved in the synthesis of amino acids and nucleic acids important for health. It plays an important role in tissues, such as: the fetus, hematopoietic system and gastrointestinal epithelium, in which cell divisions occur. For this reason, the presence of folic acid in the right amounts, ensures the proper functioning of our body. A deficiency of folic acid in the diet leads to a reduced concentration of folate in plasma and red blood cells. It is a condition that contributes to the formation of many serious diseases in our body and congenital neural tube defects in the fetus. As clinical studies have shown, the optimal concentration of folates in the blood reduces the risk of cardiovascular, circulatory, central nervous system diseases and certain types of cancer. To reduce the risk of diet-related diseases caused by folic acid deficiency, daily diet should be optimally balanced and contain products rich in natural folates. If diet is an insufficient source of folic acid, its supplementation should be considered, with the possible inclusion of its active form. Supplementation is recommended, in particular, for people with: megaloblastic anemia, diabetes mellitus, malabsorptions (e.g. Crohn's disease), alcoholism, malnutrition, neurodegenerative diseases (e.g. Alzheimer's disease), cardiovascular diseases, elevated homocysteine levels and using certain medications (e.g. oral contraceptives, metformin, methotrexate). It is also worth mentioning that metapholine supplementation bypasses the multistage metabolic process before incorporating folates into the cell cycle, as opposed to the inactive form of folic acid. This is particularly important for patients with the DHFR and MTHFR mutation, which depending on the polymorphism, may occur in up to 53% of the Caucasian population. Consequently, MTHFR reductase activity is reduced by up to 70%.